(untitled) (Romano džaniben, 2014)
Vladimír Benč – Tomáš Hrustič – Timea Kardos – Alexander Mušinka (eds.) Teoretické a praktické otázky politickej participácie Rómov na miestnej úrovni. Zborník príspevkov z medzinárodnej konferencie. /Ondřej Poduška Zuzana Bodnárová (ed.) Andi paramisi sig džal: Time goes fast in fairytales. Text collection of South Central Romani in Hungary. /Romana Hudousková Dieter W. Halwachs – Simone Klinge – Barbara Schrammel-Leber Romani: Education, Segregation and the European Charter for Regional or Minority Languages. /Marián Sloboda Barbara Schrammel-Leber – Barbara Tiefenbacher (eds.) Romani V.: Papers from the Annual Meeting of the Gypsy Lore Society /Jan Ort